Hambatan Implementasi Model Pembelajaran Project Based Learning pada Pembelajaran Sejarah Dengan Menggunakan Di Kelas XI Fase F 10 SMA Negeri 7 Padang - Perdana, Rivaldo Septa; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
Education aims to improve the quality of life of the nation through the important role of teachers and lecturers in the learning process. Effective learning should focus on modernization activities, aiming to create a creative and fun learning environment. Education is also a lifelong process to form a fully mature human being. Technology development reinforces the importance of education in shaping character and critical thinking. To achieve a good quality of education, an effective learning model is needed, such as Project Based Learning (PjBL). PjBL, as a learner-centered approach, enhances critical thinking, creativity, and problem-solving skills through real projects. This research was conducted at SMA Negeri 7 Padang, using qualitative methods with descriptive analysis. The results showed that the use of PjBL in learning history improved material understanding, critical thinking skills, collaboration, independence, creativity, learning motivation, and student learning outcomes. PjBL also provides a more authentic assessment, although it faces challenges such as time management and limited resources. This research provides evidence that PjBL can improve the quality of history learning in schools